Strategies and Techniques for Ileourethral Approximation During Robotic Intracorporeal Neobladder Reconstruction: An International Survey and Video Collection, in Collaboration with the European Association of Urology Robotic Urology Section Scientific Working Group - Maria Chiara Sighinolfi; Simone Assumma; Peter Wiklund; Richard Gaston; Andrea Minervini; Alex Mottrie; Reza Mehrazin; Abdullah Erdem Canda; Enrico Panio; Filippo Gavi; Luca Sarchi; Tommaso Calcagnile; et al. (European Urology Open Science)
Background and objective: The use of robotic-assisted radical cystectomy (RARC) with intracorporeal urinary diversion has increased rapidly in the past decade. The approximation of the ileum toward the urethral stump could be a demanding step. Whereas the techniques for reconstruction have been described in detail, a comprehensive depiction of strategies to facilitate neobladder-urethral approximation is lacking. This manuscript and video collection provide a summary of the techniques and maneuvers suggested by RARC surgeons. Methods and surgical procedure: This is a cross-sectional study in collaboration with the European Association of Urology Robotic Urology Section (ERUS) Scientific Working Group that evaluates strategies for ileourethral approximation and anastomosis from surgeons performing RARC with an intracorporeal neobladder. To this purpose, a survey was developed by a single institution with input from experts. The survey included questions on caseload, types of diversions, ileal approximation, and techniques and strategies for overcoming challenges in an ileourethral anastomosis. Responders were recruited among experts from scientific societies and were asked to rate the importance of these tricks on a Likert scale. A video collection was developed thereafter. Key findings and limitations: Twenty-one surgeons were involved, with five of them having an individual caseload of >300 cases. The Studer (n = 9) and Bordeaux (n = 9) reconstructions were most used; four operators declared the use of more than one type of diversion. Ileourethral approximation is considered a demanding part of intracorporeal neobladder reconstruction for 86% of participant surgeons. It is perceived as difficult in approximately one out of four surgical cases. Ten surgeons reported at least one conversion to ileal conduit due to impossible ileal descent. The posterior reconstruction was ranked as a useful trick to aid in an ileourethral anastomosis for ten surgeons (48%); a reduction in the Trendelenburg position by nine (43%), the use of small incisions in the mesentery was useful for six (29%) and opening the ileal segment before the anastomosis for five (24%) surgeons. Conclusions: Some strategies and techniques are available to facilitate ileal descent toward the pelvis to achieve a tension-free ileourethral anastomosis. The knowledge and application of these tricks are important to cope with this demanding step and make intracorporeal neobladder reconstruction easier and safer. Patient summary: The robotic realization of a neobladder through an intracorporeal approach could be demanding. The associated video presents some surgical strategies to make this step easier and safer, to ensure the achievement of a tension-free neobladder-urethral anastomosis.